Do Constitutions Matter? The Dilemma of a Radical Lawyer. Issue 2 (December 2019) - Shivji, Issa G.
Constitutions do not make revolutions. Revolutions make constitutions. No constitution envisages its own death, for that is what a revolution entails. But constitutions matter. Some of the finest constitutions have been erected on ugly socio-economic formations wrought with extreme inequalities and inequities. South Africa and Kenya are examples. But constitutions do matter. They rarely herald fundamental transformations. They are the product of major transformations to consolidate a new status quo. Yet, constitutions do matter. Why do they matter? Why do we need them? Why does every revolution and major change in modern societies give birth to a new constitution? This is the question I want to reflect on: why do constitutions matter?